Implementation of the Point System in Fostering the Discipline of Old Santri at Pondok Modern Darussalam Gontor Campus 7 Kalianda South Lampung: Implementasi Sistem Poin Dalam Membina Kedisiplinan Santri Lama di Pondok Modern Darussalam Gontor Kampus 7 Kalianda Lampung Selatan - Fani, Akhmad Prayogi Nur; Nugroho, Anggi Septia; Fajri, M. Rizkal (Madrosatuna: Journal of Islamic Elementary School, 2025)
This research examines the implementation of a points system to improve the discipline of old students at Pondok Modern Darussalam Gontor Campus 7 Kalianda, South Lampung. The research background involves serious problems related to discipline, including tardiness, absenteeism, and violations of internal rules. The aim of this research is to apply a point system as a solution, using a qualitative approach and descriptive methods. The research results show that the implementation of the points system has a positive impact in improving the discipline of old students, involving incentives and sanctions as an effective approach. The process of introducing the system, implementing the rules, and participation from various parties, such as teachers and student guardians, play an important role in forming a more conducive educational environment. This research provides an in-depth overview of the effectiveness of the points system in creating discipline and shaping the character of students, with regular evaluation as a basis for maintaining the sustainability of this solution in the long term.